Rubric Category of News and Articles of Islamic Navigations Occur in Surat Kabar Harian Medan - Mohd. Rafiq (Budapest International Research and Critics University, 2020)
This research was conducted on the people of Binjai City who read the daily newspapers published by Medan. Based on the scientific field, this research is a field research. This type of research is classified as quantitative research, it is correlational. Statistical testing was conducted, namely to help researchers make generalizations accurately. Using agenda setting theory was first introduced and developed by McCombs and Shaw. This theory argues that if the mass media exerts pressure on an event, then the media influences the audience. The prominence and categories of Islamic news and articles in Waspada and Analisa daily newspapers are slightly different. In the Waspada daily newspaper, articles are not only placed in the Mimbar Friday column, but also in the al-Bayan column, opinions, features, sometimes even in the editorial column. Meanwhile, there are news in almost every page of the newspaper. Waspada even prepared a column of information about Friday khatibs which occupy column two half a newspaper page. The daily newspaper Analisa rarely puts news and articles on the front page of the newspaper. Islamic articles are only placed in the Mimbar Islam column.